Letter (copy) : Spanish seamen - Tewson, Vincent
025a-0093-001 International HVT/AC/185 17th May, 1939. Mr. A. de Gondra, Basque Delegation, 14, Eccleston Sq., S.W.1. Dear Sir, Thank you for your letter of 15th May, in which you enclose list of Spanish and Basque seamen in various British ports; this list will be very useful to us and will enable us to check up the lists in our possession. In the meantime, I should like to mention for your information that of the five Spanish seamen in London whom you specify as not in receipt of assistance from us, three, namely Messrs. Eguzkiza, Larrabeiti and del Busto, are in fact receiving financial assistance from our funds. With reference to the cards for emigration to Mexico, we may say that we have received a further supply, which we shall hold here for you until such time as you can arrange to have then collected. Yours faithfully, Assistant Secretary. 292/946/25a/93